2017
DOI: 10.1097/coc.0000000000000116
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling of Tumors From Heavily Pretreated Patients With Metastatic Cancer for the Selection of Therapy

Abstract: MP-guided therapy is feasible and seems to improve the clinical outcome of extensively pretreated patients but prospective and confirmatory trials are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…In addition, the companion diagnostics to detect targets are complicated and require confirmation using prospective clinical trials. Although several pilot studies using traditional molecular profiling methods, such as polymerase chain reaction (PCR), immunohistochemistry (IHC), fluorescent in situ hybridization (FISH), and microarrays demonstrate that patients could benefit from targeted therapy (19,20), these methods have limited coverage of oncogenes and oncoproteins, and thus, the prognostic benefits of molecular profiling-based therapy have been underestimated.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the companion diagnostics to detect targets are complicated and require confirmation using prospective clinical trials. Although several pilot studies using traditional molecular profiling methods, such as polymerase chain reaction (PCR), immunohistochemistry (IHC), fluorescent in situ hybridization (FISH), and microarrays demonstrate that patients could benefit from targeted therapy (19,20), these methods have limited coverage of oncogenes and oncoproteins, and thus, the prognostic benefits of molecular profiling-based therapy have been underestimated.…”
Section: Introductionmentioning
confidence: 99%
“…The protocol followed for the obtention of the matched biopsies is the usual one at our institution and has been previously published [ 17 ]. Total RNA extraction was done with RNAeasy columns (QIAGEN), and the amount obtained was measured with the Nanodrop spectrophotometer (ND-1000).…”
Section: Patients and Methodsmentioning
confidence: 99%
“…Meta-analysis of Phase I clinical trials completed during 2011-2013 showed that overall, trials that used molecular biomarker information to influence treatment plans gave better results than trials that did not 6 . However, most precision oncology treatments utilize only one or two medicines, and resistant clones frequently emerge, emphasizing the need to deliver personalized medicine as multiple agents combined [6][7][8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%